Perceived barriers encountered by oral health professionals in the Australian public dental system providing dental treatment to individuals with special needs. (23rd February 2021) - Lim, Mathew Albert Wei Ting; Liberali, Sharon Andrea Corinne; Calache, Hanny; Parashos, Peter; Borromeo, Gelsomina Lucia
Abstract: Aims: To investigate barriers experienced by clinicians treating individuals with special needs in the Australian public dental system. Methods and results: Oral health professionals working at primary care clinics in the public dental system were invited to participate in semi‐structured interviews or focus groups to discuss the challenges they faced in managing patients with special needs. Qualitative methods, employing inductive thematic analysis, revealed two primary barriers: 1. clinicians lacked confidence in their ability to treat patients with special needs because of insufficient training and experience, and difficulties obtaining information about their patients, and 2. barriers within the public dental system, including inadequate funding, equipment and facilities, and productivity pressures prevented clinicians from being able to provide the care patients required. The priority and understanding of the oral health for these individuals within the public dental system and wider disability sector was also raised. Conclusion: A perceived lack of training and experience in managing individuals with special needs was a barrier to treating patients with special needs. Other significant barriers were under‐resourcing of the public dental system and a lack of priority and understanding regarding oral health among carers of individuals with special needs and other health professionals.